The bridge on the river Kwai - Spiegel, Sam; Lean, David; Boulle, Pierre; Columbia Pictures Production ([Burbank, Ca.] : Columbia Pictures Production, 1983)
British soldiers are forced by the Japanese to build a strategic railroad bridge. Meanwhile, the British High Command has instructed a commando team to destroy the bridge
Based on the novel by Pierre Boulle
Title from title screen
n.2 is acquisition for KPI (Kelab Pencinta Ilmu)
Academy Awards: Best Picture; Best Screenplay, Carl Foreman (credited as Michael Wilson); Best Director, David Lean; Best Cinematography, Jack Hildyard; Best Score, Malcolm Arnold; Best Actor, Alec Guinness. Academy Award nomination: Best Supporting Actor, Sessue Hayakawa
Screenplay, Pierre Boulle
Cast : William Holden, Alec Guinness, Jack Hawkins, Sessue Hayakawa, James Donald
Keywords: Burma -- Siam Railroad -- Drama; World War, 1939-1945 -- Drama; War films